Learning Situations about Digitalization. Development of a Workshop Using Learning, Leadership and Storytelling Theories - Braun, Greta; Falegård, Johan (My University, 2019)
With the great need to stay competitive on the global market in the manufacturing industry, constant efficiency improvements are required. This paves the way for a new industrial revolution: digitalization. Therefore, the need for knowledge and experience about the possibilities and challenges of digitalization is vital. Projects like Smarta Fabriker with the purpose to disseminate knowledge about digitalization to companies and schools as the next generation employees are conducted to fulfil these needs. The Smarta Fabriker project offers an activity-based workshop experience that teaches about digitalization topics. This thesis focuses on the development of a workshop as a learning situation together with the project Smarta Fabriker. The workshop is developed with application of theories that promote learning and knowledge transfer and its performance is tested and evaluated to identify the benefits of the new workshop. The new workshop is evaluated in comparison to Smarta Fabriker’s already existing workshop to be able to distinguish improvements with the new workshop. The evaluation shows that the participants remember more of the content of the new workshop than of the former one, two weeks after the workshop. Furthermore, the participants claim that they experienced the new workshop as rewarding. However, the results show no statistical significance according to the performed tests due to the low number of participants in the evaluation. The results show only trends of what is the contribution of the applied theories of learning regarding increased learning. Therefore, no general conclusion can be made without further investigation.
Keywords: learning; leadership; workshop; storytelling; teaching competencies; digitalization